YAP1 Promotes Tumor Invasion and Metastasis in Nasopharyngeal Carcinoma with Hepatitis B Virus Infection - Huang, Zeli (Onco Targets Ther, 2020)
INTRODUCTION: Nasopharyngeal carcinoma (NPC) patients with HBsAg (+) commonly present with high frequencies of distant metastasis and poor survival rate; however, the mechanism has not been elucidated. MATERIALS AND METHODS: We analyzed the yes-associated protein 1 (YAP1) expression between HBsAg (+) and HBsAg (-) of NPC patients, then analyzed the relationship of YAP1 with survival. We further explored the anti-tumor role in NPC cell lines using YAP1 siRNA technique, and checked whether YAP1 regulatesepithelial–mesenchymal transition ( EMT). The relationship between HBV X protein (HBx) and YAP1 was also tested using Dual-Luciferase reporter assay. Finally, we explored anti-YAP1 to inhibit tumor metastasis using the xenograft mice model. RESULTS: In the current study, we found that YAP1 expression was higher in HBsAg (+) samples than in the HBsAg (-) samples, as a clinical signature, suggesting that YAP1 could be used as a prognostic factor for NPC. Our results showed that the HBx could regulate YAP1, further promoting cellular invasiveness through EMT. Anti-YAP1 can also decrease metastasis in vivo. CONCLUSION: Our findings suggest that YAP1 is a promising prognostic factor in NPC and could be used as a potential treatment target for NPC with HBV infection.